Mathematical Representations Based on Field-Dependent and Field-Independent Cognitive Styles - Sobirin, Juliyat Hadi; Setiawan, Yayan Eryk; Faradiba, Surya Sari (Universitas Sembilanbelas November Kolaka, 2023)
Mathematical representation ability is very important for students, but many students still need to be able to solve mathematical problems with various mathematical representation abilities. This research is narrative research with a qualitative approach to describe the problems of students' mathematical representation abilities in terms of field-dependent and field-independent cognitive styles on the set topic. A total of 4 students, based on the GEFT test and the results of the subject teacher's directions, tended to field-dependent and field-independent cognitive styles. The instruments used in this study were the GEFT test, questions of representation ability, and interview guidelines. The results of the data analysis show that the mathematical representation abilities of students with a field-dependent cognitive style can represent with several models. In contrast, the mathematical representation abilities of students with a field-independent cognitive style can represent all indicators. Based on these conditions, in the learning process, the teacher can plan a differentiated lesson by paying attention to the differences in students' cognitive styles.